O mito alegórico como fonte de sensibilização para filosofar: a fábula educativa em Platão e Harry Potter - FERNANDA LAIS DA SILVA CARNEIRO DOS SANTOS (2020)
This dissertation intends to show a source of sensitization to philosophize in order to arouse the interest of the youngest. Using philosophizing through metaphor, allegory, fantasy and myth. Some well-known thinkers make use of allegorical myth as a metaphorical philosophy, that is, myth (or part of it) may not be as separate from logos, as philosophy manuals say. This dissertation wants to resume, that even the greatest representative of the classic and supposedly critical tradition of mythology, Plato, does not totally break with the myth, on the contrary, the characters of his work use it to raise philosophical reflections and do it with great success. If the traditional path of discourse has been developed and explored for a long time, perhaps we can take a “new route”, or rather, renew an old route. Behind books that seem like simple “stories”, for example, the Harry Potter saga, it is possible to see representations that bring philosophical reflections in an analogous way and with spontaneity, that transform the way of seeing the lives of many of its readers. Is it possible, then, that author J.K Rowling uses the same means as Plato? Through theoretical research and development of the practical part through the use of excerpts from films and educational games based on Harry Potter and the philosophy behind the pages and scenes, the dialogue of philosophy present in the saga was introduced, being it a kind of representative contemporary allegorical myth as a path to teaching. The final product is a script of the classes, carried out during the application of the practical part, to start these classes a didactic game was created. A video channel on the subject was also started, as complementary material.